The Risk Factors Causes Incidence of HIV/AIDS for Peoples Living with HIV/AIDS (PLWHA) : A Systematic Review (American Journal of Arts and Human Science, 2023)
Human Immunodeficiency Virus (HIV) is an infectious disease leading to the top level of cause of died with high mortality and morbidity rates and requires relatively long diagnosis and therapy. HIV is a virus that attacks white blood cells (lymphocytes) in the body. which causes a decrease in human immunity, causing Acquired Immunodeficiency Syndrome (AIDS) (Dwi Astuti, 2022). In Indonesia, the number of positive HIV cases has been increasing yearly, and it mostly affects the productive age group, specifically individuals aged 25-49 years. HIV is a virus that weakens the human immune system. The occurrence of HIV is influenced by various factors contributing to its spread. This study aims to identify the risk factors associated with HIV incidence in Indonesia. The methodology involves a literature review, examining the risk factors for HIV incidence based on ten health journals published in the last ten years, following specific inclusion and exclusion criteria. Based on the reviewed journals, the risk factors for HIV incidence in Indonesia are as follows: male gender (OR=1.77), age